Effect of Street Vending on Small and Medium Enterprises Performance - Isaac Iortimbir Aun; Olumide Elijah Salami (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
Despite the tough circumstances and competitiveness of shops with permanent structures, it is acknowledged that street enterprise could play a vital role in alleviating poverty across the globe. Formal organizations recognize this possibility and are strategically incorporating informal organizations into their selling operations. The broad objective of this study was to examine the effect of street trade on small and medium enterprises performance with a specific focus on the operators in Ilorin metropolis. Therefore, the study’s specific objectives were to: determine the relationship between street entrepreneurship transformative measures and market share of SMEs and evaluate the effect of transformative measures on the transformation of street entrepreneurship into SMEs. Since the study population was large and unknown, Cochran sample size formula was used to determining the sample size of 385. A questionnaire was designed using structured questions to obtain primary data from the respondents in Ilorin metropolis, Kwara State. A total of three hundred and eighty-five (385) copies of the questionnaire were administered, out of which three hundred and sixty-eight (368) copies were properly filled and returned. The formulated hypotheses were tested using multiple regression analysis and correlation with the aid of SPSS version 21. The findings of the study revealed that; the strong positive relationship between street entrepreneurship transformative measures with socio-cultural factor as the highest correlation coefficient of .946, multiple regression analysis established that transformative measures have an effect on the transformation of street entrepreneurship with an R2 value of .987. Hence, the study concluded that all transformative measures of street entrepreneurship have a significant effect on market share and that transformative measures have a significant positive effect on the transformation of street entrepreneurship into SMEs. It was recommended that street entrepreneurs should not underestimate the potential of relationship marketing, which may increase a company’s financial performance. Moreover, street entrepreneurial ventures should concentrate on changing their enterprises into SMEs by gaining a deeper understanding, learning skills, and developing a working knowledge of all aspects that may impact their operations and thwart their transformative aims.